2003
DOI: 10.1242/dev.00394
|View full text |Cite
|
Sign up to set email alerts
|

Knock-in of integrin β1D affects primary but not secondary myogenesis in mice

Abstract: Integrins are extracellular matrix receptors composed of α and β subunits involved in cell adhesion, migration and signal transduction. The β1 subunit has two isoforms, β1A ubiquitously expressed and β1D restricted to striated muscle. They are not functionally equivalent. Replacement of β1A by β1D (β1D knock-in) in the mouse leads to midgestation lethality on a 50% Ola/50% FVB background [Baudoin, C., Goumans, M. J., Mummery, C. and Sonnenberg, A. (1998). Genes Dev. 12, 1202-1216]. We crossed the β1D knock-in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 67 publications
0
22
0
Order By: Relevance
“…Although a5b1, a4b1 and av integrins are not essential for myogenic cell fusion itself in vitro (Yang et al, 1996;Blaschuk et al, 1997;Taverna et al, 1998), cell engagement with the fibronectin matrix present within the myotome in vivo may serve to promote the approximation of myogenic cells, increasing the opportunities for fusion. The fact that b1D integrin knock-in and conditional b1 integrin knock-out mouse embryos show defects in myotube formation (Cachaço et al, 2003;Schwander et al, 2003) supports this hypothesis.…”
Section: Developmental Dynamicsmentioning
confidence: 70%
“…Although a5b1, a4b1 and av integrins are not essential for myogenic cell fusion itself in vitro (Yang et al, 1996;Blaschuk et al, 1997;Taverna et al, 1998), cell engagement with the fibronectin matrix present within the myotome in vivo may serve to promote the approximation of myogenic cells, increasing the opportunities for fusion. The fact that b1D integrin knock-in and conditional b1 integrin knock-out mouse embryos show defects in myotube formation (Cachaço et al, 2003;Schwander et al, 2003) supports this hypothesis.…”
Section: Developmental Dynamicsmentioning
confidence: 70%
“…Mice homozygous for this mutation showed multiple defects in development and embryonic lethality around day 11.5 . Later experiments suggested compromised nutrition of the embryo caused by malformation of the placenta and decreased muscle formation (both tissues showing exclusive expression of the b1A isoform in wild type) to be the main reasons for the embryonic lethality (Cachaco et al 2003). Interestingly, some features of the defects observed in development of the neuronal tube resembled those found in Fibronectin deficient embryos (George et al 1993), which points to an essential interaction between Integrin b1A and Fibronectin in this process.…”
Section: Mice With Targeted Disruption Of a Specific Protein Isoformmentioning
confidence: 99%
“…Indeed, it was shown that the expression of CD9, the integrin-associated tetraspanin that regulates in vitro myoblast and sperm-egg fusion [104], was strongly reduced on the surface of β1-deficient myoblasts [101]. Furthermore, analysis of knockin embryos in which β1D had been replaced by β1A [105] revealed a reduction in skeletal muscle mass, when the mice were bred on a predominantly FVB background [106]. This reduction appeared to be due to impaired primary myogenesis, whereas there was no direct effect on secondary myogenesis.…”
Section: Skeletal Musclementioning
confidence: 99%
“…The use of cultured β1-null progenitor cells and the analysis of β1 chimeric mice have shown that β1 integrins are required for colonization of the fetal haematopoietic organs but not for the development of haematopoietic stem cells within those organs [105]. Studies using mice chimeric for either the α4, α5, or αv subunit, which are the β1-associated α subunits on leucocyte progenitors, indicate that none of these integrins is required for colonization of the fetal haematopoietic organs but they do implicate α4 in the multilineage development of haematopoietic cells and in lymphocyte homing to lymph nodes and Peyer's patches [106,107].…”
Section: Haematopoietic Cellsmentioning
confidence: 99%